The Customers’ Perception on English for Branding: A Study in a Non-English Speaking Area - Rahmi Fhonna; Fidyati Fidyati (Proceedings of AICS - Social Sciences, 2018)
Language is still believed as a tool to connect people which can be shown both verbally and non-verbally (Pan: 2014). In marketing world nowadays, marketers and costumers demonstrate positive trends in engaging each other. This research presents the perception of the customers towards the use of English for branding in one of non-English speaking areas in Aceh, Indonesia. 33 randomly-chosen respondents of 11 males and 22 females participated in this study. They were provided with a set of questionnaire consisting of a series of question. The result presented that most of the participants show positive responses towards the issue of using English for branding. 63.64% of respondents agree that the use of English for branding may increase their English vocabularies. In addition, 51.52% of them feel curios towards the products offered in the store of English branding. However, 45.45% of the respondents seems disagree that the use of English for branding may influence the cost and profits of the stores. Shortly, most participants provide positive comments toward the issue of this study.Keywords:language, branding, customers.